2012
DOI: 10.1103/physrevb.85.195134
|View full text |Cite
|
Sign up to set email alerts
|

Electronic-structure origin of the anisotropic thermopower of nanolaminated Ti3SiC2determined by polarized x-ray spectroscopy and Seebeck measurements

Abstract: Nanolaminated materials exhibit characteristic magnetic, mechanical, and thermoelectric properties, with large contemporary scientific and technological interest. Here we report on the anisotropic Seebeck coefficient in nanolaminated Ti 3 SiC 2 single-crystal thin films and trace the origin to anisotropies in element-specific electronic states. In bulk polycrystalline form, Ti 3 SiC 2 has a virtually zero Seebeck coefficient over a wide temperature range. In contrast, we find that the in-plane (basal ab) Seebe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
26
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 39 publications
5
26
0
Order By: Relevance
“…Alternately two dimensionality of the electronic structure, leading to open Fermi surfaces when doped can lead to this type of behavior. 37,38 This is the case here. Thus both the conductivity and thermopower indicate practically two dimensional transport for p-type samples.…”
Section: B Thermoelectric Propertiesmentioning
confidence: 58%
“…Alternately two dimensionality of the electronic structure, leading to open Fermi surfaces when doped can lead to this type of behavior. 37,38 This is the case here. Thus both the conductivity and thermopower indicate practically two dimensional transport for p-type samples.…”
Section: B Thermoelectric Propertiesmentioning
confidence: 58%
“…This explanation is coherent with Ti 3 SiC 2 Seebeck coefficient data which were recently published. 21 The resistivity measurements also clearly evidence a strong anisotropy of Ti 2 AlC electronic properties. Comparing the data recorded on the thin film to those obtained on the bulk sample, which are interpreted in terms of an effective medium approach, it is shown that the room temperature resistivity ρ zz is more than one order of magnitude larger than ρ xx .…”
Section: Discussionmentioning
confidence: 82%
“…This was demonstrated by Chaput et al who showed that the negligible Seebeck coefficient of a polycrystalline Ti 3 SiC 2 sample could be understood from the compensation of electronlike states along the c axis by holelike states within the basal plane orientation at the Fermi level. 5,20,21 An accurate description of both the electronic structure and the transport properties is all the more desirable that MAX phases exhibit complex Fermi surfaces with generally more than two bands [see Fig. 1(b) for Ti 2 AlC], 22 and that the chemical bonding in these materials is based on complex charge transfers involving metallic, ionic, and covalent bonds.…”
Section: Introductionmentioning
confidence: 99%
“…The MAX phases have been extensively studied not only in order to shed light on their unique combination of properties but also to explore their potential for numerous industrial applications (see review articles [1,2,3,4] and recent examples [5,6,7,8,9,10,11,12,13]). It has long been appreciated that a promising strategy to tailor properties is to form solid solutions on the M, A and/or X sites [1,2].…”
Section: Introductionmentioning
confidence: 99%